IEM-WE on Bandwagon to Dabong School which was affected by floods - Habibah @ Norehan, Hj. Haron, Dr (The Institution of Engineers, Malaysia (IEM), 2019)
Link to publisher’s homepage at https://www.myiem.org.my/